Safety and efficacy of erythropoietin for the treatment of patients with optic neuritis (TONE): a randomised, double-blind, multicentre, placebo-controlled study. Issue 12 (December 2021) - Lagrèze, Wolf A; Küchlin, Sebastian; Ihorst, Gabriele; Grotejohann, Birgit; Beisse, Flemming; Volkmann, Martin; Heinrich, Sven P; Albrecht, Philipp; Ungewiss, Judith; Wörner, Michael; Hug, Martin J; Wolf, Sebastian; et al.
Summary: Background: The human cytokine erythropoietin conveys neuroprotection in animal models but has shown ambiguous results in phase 2 clinical trials in patients with optic neuritis. We assessed the safety and efficacy of erythropoietin in patients with optic neuritis as a clinically isolated syndrome in a multicentre, prospective, randomised clinical trial. Methods: This randomised, placebo-controlled, double-blind phase 3 trial, conducted at 12 tertiary referral centres in Germany, included participants aged 18–50 years, within 10 days of onset of unilateral optic neuritis, with visual acuity of 0·5 or less, and without a previous diagnosis of multiple sclerosis. Participants were randomly assigned (1:1) to receive either 33 000 IU erythropoietin or placebo intravenously for 3 days as an adjunct to high-dose intravenous methylprednisolone (1000 mg per day). Block randomisation was performed by the trial statistician using an SAS code that generated randomly varying block sizes, stratified by study site and distributed using sealed envelopes. All trial participants and all study staff were masked to treatment assignment, except the trial pharmacist. The first primary outcome was atrophy of the peripapillary retinal nerve fibre layer (pRNFL), measured by optic coherence tomography (OCT) as the difference in pRNFL thickness between the affected eye at week 26 and the unaffected eye at baseline. The second primary outcome was low contrast letter acuity at week 26, measured as the 2·5% Sloan chart score of the affected eye. Analysis was performed in the full analysis set of all randomised participants for whom treatment was started and at least one follow-up OCT measurement was available. Safety was analysed in all patients who received at least one dose of the trial medication. This trial is registered at ClinicalTrials.gov, NCT01962571 . Findings: 108 participants were enrolled between Nov 25, 2014, and Oct 9, 2017, of whom 55 were assigned to erythropoietin and 53 to placebo. Five patients were excluded from the primary analysis due to not receiving the allocated medication, withdrawn consent, revised diagnosis, or loss to follow-up, yielding a full analysis set of 52 patients in the erythropoietin group and 51 in the placebo group. Mean pRNFL atrophy was 15·93 μm (SD 14·91) in the erythropoietin group and 14·65 μm (15·60) in the placebo group (adjusted mean treatment difference 1·02 μm; 95% CI −5·51 to 7·55; p=0·76). Mean low contrast letter acuity scores were 49·60 (21·31) in the erythropoietin group and 49·06 (21·93) in the placebo group (adjusted mean treatment difference −4·03; −13·06 to 5·01). Adverse events occurred in 43 (81%) participants in the erythropoietin group and in 42 (81%) in the placebo group. The most common adverse event was headache, occuring in 15 (28%) patients in the erythropoietin group and 13 (25%) patients in the placebo group. Serious adverse events occurred in eight (15%) participants in the erythropoietin and in four (8%) in the placebo group. One patient (2%) in the erythropoietin group developed a venous sinus thrombosis, which was treated with anticoagulants and resolved without sequelae. Interpretation: Erythropoietin as an adjunct to corticosteroids conveyed neither functional nor structural neuroprotection in the visual pathways after optic neuritis. Future research could focus on modified erythropoietin administration, assess its efficacy independent of corticosteroids, and investigate whether it affects the conversion of optic neuritis to multiple sclerosis. Funding: German Federal Ministry of Education and Research (BMBF).